问题 解答题
脱式计算,怎样简便就怎样算.
23×
14
39
+14×
16
39
14
3
17
-6.46-3.54
1
13
+
12
13
×(
5
2
-
1
3
3
13
×
3
4
+
10
13
÷
4
3
3×(
2
15
+
1
12
)-
1
4
(1
2
3
-1
2
5
)÷(6-
2
7
)×4
2
7
答案

(1)23×

14
39
+14×
16
39

=

14
39
×(23+16)

=

14
39
×39

=14;

(2)14

3
17
-6.46-3.54

=14

3
17
-(6.46+3.54)

=14

3
17
-10

=4

3
17

(3)

1
13
+
12
13
×(
5
2
-
1
3

=

1
13
+
12
13
×
5
2
-
12
13
×
1
3

=

1
13
+
30
13
-
4
13

=

27
13

(4)

3
13
×
3
4
+
10
13
÷
4
3

=

3
13
×
3
4
+
10
13
×
3
4

=

3
4
×(
3
13
+
10
13
)

=

3
4

(5)3×(

2
15
+
1
12
)-
1
4

=

2
15
+3×
1
12
-
1
4

=

6
15
+
1
4
-
1
4

=

2
5

(6)(1

2
3
-1
2
5
)÷(6-
2
7
)×4
2
7

=1

4
15
÷5
5
7
×4
2
7

=

19
15
×
7
40
×
30
7

=

19
20

单项选择题
判断题